2014
DOI: 10.3329/pa.v24i1-2.19102
|View full text |Cite
|
Sign up to set email alerts
|

Protection Effect of Vaxxitek HVT + IBD Vaccine Against Infectious Bursal Disease in Broiler Chickens

Abstract: The very virulent infectious bursal disease virus (vvIBDV) infection cause constant and frequent outbreaks of IBD. In order to prevent the disease caused by vvIBDV, moderate-virulent live vaccines are usually used in broilers, but these vaccine influence the immune system of chickens and cause the immunosuppression. VAXXITEK ® HVT+IBD bivalent vaccine, a novel vaccine produced by Merial Company, is the recombinant vaccine generated by inserting IBDV VP2 gene into the HVT genome. The recombinant vaccine could p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
4
5
0
1
Order By: Relevance
“…Similarly, group A had the lowest histopathological lesion score of bursa post challenge. All of these reflect the superiority of the vaccine used in this group in protection against the vvIBDV challenge; similar findings were reported by Le Gros et al [42], Sultan et al [54], and Rashid [55].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similarly, group A had the lowest histopathological lesion score of bursa post challenge. All of these reflect the superiority of the vaccine used in this group in protection against the vvIBDV challenge; similar findings were reported by Le Gros et al [42], Sultan et al [54], and Rashid [55].…”
Section: Discussionsupporting
confidence: 88%
“…Independence of FCR was recorded in all groups during the challenge period (seven days); groups A and B showed the best FCR and similar results were described by Rashid [55].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Szczepionka może być podana in ovo (na 3 dni przed wylęgiem) lub podskórnie w pierwszej dobie życia, w obecności nawet wysokich mian przeciwciał matczynych. Badania wykazały, że szczepionka nie powoduje zmian w bursie Fabrycjusza, a co za tym idzie -immunosupresji (12,86). Zakażenie kontrolne immunizowanych szczepionką wektorową kurcząt SPF wykazało, że zapewnia ona protekcję sięgającą 95-100% przed wirusami o różnej zjadliwości (vvIBDV, cIBDV, vIBDV pochodzące ze Stanów Zjednoczonych) (12).…”
Section: Zwalczanie Zakaźnego Zapaleniaunclassified
“…However, in experiments presented here, 2 out of 10 birds in groups G3 and G4 had symptoms of acute IBD, and had succumbed to the infection It has been established recently that even in the presence of high titers of maternal antibodies, the recombinant vaccine (vHVT13) was efficiently protecting chicks against classical, very virulent and variant IBDv (Bublot et al, 2007, Perozo et al, 2009, Prandini et al, 2016. A few experiments with the rHVT-IBDv have been done in commercial broilers and a good antibody response to IBDv was obtained in the research work conducted in Italy (Le Gros et al, 2009), Slovenia (Zorman-Rojs et al, 2011 and Jhenaidha (Rashid et al, 2013) after a subcutaneous application and when the in ovo vaccine delivery system was used (Roh et al, 2016). It was also shown that the recombinant VAXXITEK HVT-IBDv vaccine provided a high maternal antibody titer in progeny from parents vaccinated with a single recombinant vaccine or if the rHVT-IBDv vaccine was combined with the inactivated vaccine, compared to a single inactivated vaccine.…”
Section: Figurementioning
confidence: 99%